Writing right for today's mass media : - Adams, Paul (Nelson-Hall Publishers, 1998)
This unique writing text and workbook format furniahes everything a student needs while learning to write for the mass media. Built around the concept that mass media writing can be enjoyable and rewarding, part one covers writing news stories for both print and broadcast, as well as persuasive writing, advertising, and public realtions. More than one hundred individual assignments are provided in these areas. Part two gives students practice and confidence in their writing and language skills. Numerous pages of language drills and exercises cover key areas such as: vivid verbs, homophones, concrete words, misplaced modifiers, gobbledygook, sexism, numbers, agreement, active voice, and more